Parallel changes of proinsulin and islet amyloid polypeptide in glucose intolerance. - MacNamara, C; Barrow, B; Manley, SE; Levy, J; Clark, A; Turner, R (2000)
Elevated proinsulin secretion and islet amyloid deposition are both features of Type 2 diabetes but their relationship to beta-cell dysfunction is unknown. To determine if islet amyloid polypeptide (IAPP) secretion is disproportionate with other beta-cell products at any stage of glucose intolerance, 116 subjects were studied. Non-diabetic subjects with equivalent body mass index (BMI) were assigned to three groups, (i) normal fasting glucose, fpg<5.5 mmol l(-1); (ii) intermediate fasting glucose, fpg> or =5.5<6.15 mmol l(-1); (iii) impaired fasting glucose (IFG), fpg> or =6.1<7.0 mmol l(-1). Diabetic subjects were divided according to therapy (9 diet, 19 tablet, and 11 insulin). IAPP, C-peptide and proinsulin were measured fasting and at the end of a 1-h glucose infusion. Fasting C-peptide, IAPP and proinsulin were significantly elevated in the IFG group compared with the other non-diabetic groups (P<0.02); fasting IAPP/C-peptide and proinsulin/C-peptide were 1-2% in all non-diabetic groups. Fasting and 1-h proinsulin and proinsulin/C-peptide were higher in diabetic compared with non-diabetic subjects (P<0.01). IAPP and IAPP/C-peptide in diabetic groups were similar to that in non-diabetic subjects but reduced in the insulin-treated group (P<0.01). Proinsulin was disproportionately increased compared with C-peptide and IAPP in Type 2 diabetes particularly in severe beta-cell failure implying more than one concurrent beta-cell pathology.